Propagation of the main signal in a dispersive Lorentz medium - Ciarkowski, A. (Archives of Acoustics, 2002)
Evolution of the main signal in a Lorentz dispersive medium is considered. The signal propagating in the medium is excited by a sine-modulated pulse signal, with its envelope described by a hyperbolic tangent function. Both uniform and non-uniform asymptotic representations for the signal are found. It is shown how the uniform representation reduces to the non-uniform one. The results obtained are illustrated with a numerical example.